2015
DOI: 10.1038/srep14506
|View full text |Cite
|
Sign up to set email alerts
|

Universal electronic structure of polar oxide hetero-interfaces

Abstract: The electronic properties of NdGaO3/SrTiO3, LaGaO3/SrTiO3, and LaAlO3/SrTiO3 interfaces, all showing an insulator-to-metal transition as a function of the overlayer-thickness, are addressed in a comparative study based on x-ray absorption, x-ray photoemission and resonant photoemission spectroscopy. The nature of the charge carriers, their concentration and spatial distribution as well as the interface band alignments and the overall interface band diagrams are studied and quantitatively evaluated. The behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
2
16
0
Order By: Relevance
“…Charge transfer to or from semiconducting or insulating materials has also been investigated at various, different heterojunctions, and in some cases, it was demonstrated that even a two‐dimensional metal can be realized at some of these heterointerfaces as a consequence of the charge transfer. Famous examples comprise polar oxide interfaces (LaAlO 3 /SrTiO 3 or LaGaO 3 /SrTiO 3 ) or purely organic interfaces such as TTF/TCNQ (tetrathiofulvalene/tetracyanoquinodimethane) or rubrene/F 16 CoPc (rubrene/fluorinated cobalt phthalocyanine) . Such two‐dimensional electron systems confined to an interface can exhibit fascinating physical properties and, therefore, are of particular interest to fundamental as well as applied research.…”
Section: Introductionmentioning
confidence: 99%
“…Charge transfer to or from semiconducting or insulating materials has also been investigated at various, different heterojunctions, and in some cases, it was demonstrated that even a two‐dimensional metal can be realized at some of these heterointerfaces as a consequence of the charge transfer. Famous examples comprise polar oxide interfaces (LaAlO 3 /SrTiO 3 or LaGaO 3 /SrTiO 3 ) or purely organic interfaces such as TTF/TCNQ (tetrathiofulvalene/tetracyanoquinodimethane) or rubrene/F 16 CoPc (rubrene/fluorinated cobalt phthalocyanine) . Such two‐dimensional electron systems confined to an interface can exhibit fascinating physical properties and, therefore, are of particular interest to fundamental as well as applied research.…”
Section: Introductionmentioning
confidence: 99%
“…This uncompensated field could be due to the partial filling of LAO surface oxygen vacancies (which have been suggested as the driver behind electronic reconstruction) [71] when exposed to oxygen atmosphere. [66] The BE of the low-BE-Sr component is at a highly unusual value, as throughout the current literature secondary components in STO based systems are almost exclusively reported at the higher BE side with respect to bulk STO. [44,60,61] Exotic defect states, such as complex Sr/Ti anti-site defects were reported to yield low BEs, [72] but these are unlikely to form in a reversible manner under the light thermodynamic treatments in our study.…”
Section: Doi: 101002/adma202004132mentioning
confidence: 90%
“…This uncompensated field could be due to the partial filling of LAO surface oxygen vacancies (which have been suggested as the driver behind electronic reconstruction) [ 71 ] when exposed to oxygen atmosphere. [ 66 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…By using solid solutions like La x Sr 2y Al x+y Ta y O 3 or (LaAlO 3 ) 0.5 (SrTiO 3 ) 0.5 , the polar discontinuity can be weakened, leading to a higher critical thickness and an alteration of interface properties (111)(112)(113). All these systems may have different properties emerging from the interaction of the SrTiO 3 surface with the (polar) overlayer, although their electronic structure is remarkably similar (114). Therefore, studying the SrTiO 3 surface states that form at the interface with LaAlO 3 should yield results applicable to all such interfaces.…”
Section: Tunable Interface Properties By Overlayer Growthmentioning
confidence: 99%